DAMPAK PERSEPSI DUKUNGAN ORGANISASI DAN KARATERISTIK PEKERJAAN TERHADAP KNOWLEDGE SHARING: PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARABEL MEDIASI - Tri Sukma; Fitri Handayani; Sefnedi Sefnedi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
Organizational citizenship behavior has been recognized as an important variable for every organization both in academicians and practitioners. The purpose of this study is to investigate the role of organizatinal citizenship behavior as mediator on the relationship between perceived organizational support, job characteritics and knowledge sharing. The number of respondents in this study was 37 employees of the Civil Servants in the Public Works and Public Housing Agency of the West Sumatra Region of Padang City. The results of analysis revealed that perceived organizational support and job characteristics did not affect directly knowledge sharing. However, perceived organizational support was found to have positive effect on organizational citizenship behavior while job characteristics did not influence organizational citizenship behavior. Furthermore, organizational citizenship behavior was found to have positive effect on knowledge sharing. In addition, organizational citizenship behavior was proven to mediate the relationship between perceived organizational support and knowledge sharing. However, it did not mediate the relationship between job characteristics and knowledge sharing.